2003
DOI: 10.1161/01.cir.0000054781.50889.0c
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Atherogenesis in Mice by Switching Off Hepatic Lipoprotein Secretion

Abstract: Background-LDL receptor-deficient "apolipoprotein (apo)-B100 -only" mice (Ldlr Ϫ/Ϫ Apob 100/100 have elevated LDL cholesterol levels on a chow diet and develop severe aortic atherosclerosis. We hypothesized that both the hypercholesterolemia and the susceptibility to atherosclerosis could be eliminated by switching off hepatic lipoprotein production. Methods and Results-We bred LdlrϪ/Ϫ Apob 100/100 mice that were homozygous for a conditional allele for Mttp (the gene for microsomal triglyceride transfer protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 27 publications
7
110
1
Order By: Relevance
“…Cholesterol levels do not drop in apoE Ϫ/Ϫ recipients (12). Transfer of these lesion-rich aortic arches into WT recipients (C57BL͞6 apoE ϩ/ϩ ) results in an immediate conversion to normal lipid profiles, which in turn promotes lesion regression (12), in agreement with nonsurgical methods that restore normal blood lipid profiles and͞or apoE (23,24). Significant changes in lesion area were observed by or before 2 weeks after surgical transfer (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Cholesterol levels do not drop in apoE Ϫ/Ϫ recipients (12). Transfer of these lesion-rich aortic arches into WT recipients (C57BL͞6 apoE ϩ/ϩ ) results in an immediate conversion to normal lipid profiles, which in turn promotes lesion regression (12), in agreement with nonsurgical methods that restore normal blood lipid profiles and͞or apoE (23,24). Significant changes in lesion area were observed by or before 2 weeks after surgical transfer (Fig.…”
Section: Resultssupporting
confidence: 68%
“…A reduction in HDL has also been observed in Pcsk9-deficient mice (3), and those authors suggested that this results from enhanced clearance of apoE-containing lipoproteins facilitated by increased hepatic LDLR abundance. Furthermore, Lieu et al (10) reported similar findings in Reversa mice and suggested that HDL particle formation requires components derived from apoB-associated lipoproteins. Serum free cholesterol and phospholipids were reduced as well [25% (P , 0.005) and 54% (P , 0.0001), respectively].…”
Section: Suppression Of Hepatic Pcsk9 Mrna Increases Hepatic Ldlr Promentioning
confidence: 72%
“…In the same report, Crooke reported that Apoe -defi cient mice were the least sensitive to the lipid-lowering effects of ApoB ASO, with serum TC being reduced by 25% and LDL by 40%. It has been suggested that mature HDL particles require components of apoB-containing lipoproteins, so that a signifi cant loss of VLDL and LDL results in a reduction in the number of HDL particles ( 36 ). Alternatively, reduction in the secretion of hepatic ApoB may allow secreted ApoE to associate more readily with HDL particles in circulation and thus redirect HDL particles to a clearance via LDL receptors.…”
Section: Discussionmentioning
confidence: 99%